Sense of place attachment of user in public open space commercial building in West Jakarta - Anggiani M.; D Ayudya R.; Hirda A. (BIO Web of Conferences)
The existence of public spaces dates back to Ancient Roman, Greek, and the present day. Although people today are known for their individualistic attitudes, they still need a place to communicate. However, public space is present everywhere possible, one of which is currently in place owned by the private sector. The presence of public spaces by the user is significant because, without users, public spaces would not “live.” The presence of visitors in a public place may be due to the visitor’s need for an activity in that place or the absence of a necessity. This study uses quantitative research to discuss visitors’ attachment to public open spaces. Research results show visitors attach to different affective and functional relationships with public spaces. Visitors’ functional links to public spaces are superior to emotional connections. Overall, this study shows visitors feel engaged with the public search space. Some things don’t make visitors feel connected regarding their internal relationship to the public space. This research is helpful for designers of public spaces in private spaces to realize designs that are appealing to their visitors. This research can contribute to creating more inclusive, resilient, and sustainable urban environments, aligning with the SDGs 11, 3, 8, and 9.